2005
DOI: 10.1101/gad.1257405
|View full text |Cite
|
Sign up to set email alerts
|

To proliferate or to die: role of Id3 in cell cycle progression and survival of neural crest progenitors

Abstract: The neural crest is a unique population of mitotically active, multipotent progenitors that arise at the vertebrate neural plate border. Here, we show that the helix-loop-helix transcriptional regulator Id3 has a novel role in cell cycle progression and survival of neural crest progenitors in Xenopus. Id3 is localized at the neural plate border during gastrulation and neurulation, overlapping the domain of neural crest induction. Morpholino oligonucleotide-mediated depletion of Id3 results in the absence of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 57 publications
4
86
1
Order By: Relevance
“…For example, it is clear that induction of Msx1 and Zic1/Pax3/7 represent independent events in the frog (3,4,22). Although classified as neural crest specifier genes, c-Myc, Id, and AP-2 are first deployed at the neural plate border of the early neurula, rather than in nascent neural crest cells (23)(24)(25)(26)(27)(28)(29). Because recent studies suggest that onset of neural crest formation and specifier expression in both frog and chick may occur in the gastrula, these genes may act earlier in neural crest specification than formerly assumed.…”
Section: Temporal Sequence Of Neural Plate Border and Early Neural Crmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is clear that induction of Msx1 and Zic1/Pax3/7 represent independent events in the frog (3,4,22). Although classified as neural crest specifier genes, c-Myc, Id, and AP-2 are first deployed at the neural plate border of the early neurula, rather than in nascent neural crest cells (23)(24)(25)(26)(27)(28)(29). Because recent studies suggest that onset of neural crest formation and specifier expression in both frog and chick may occur in the gastrula, these genes may act earlier in neural crest specification than formerly assumed.…”
Section: Temporal Sequence Of Neural Plate Border and Early Neural Crmentioning
confidence: 99%
“…The second peak only becomes evident after E4. 25. The first peak in expression of MsxA, AP-2, ZicA, Id, and Pax3/7 most likely corresponds to different roles these genes play during gastrulation (i.e., prominent presence of MsxA activity in the lateral mesoderm, as shown by in situ analysis).…”
Section: Temporal Sequence Of Neural Plate Border and Early Neural Crmentioning
confidence: 99%
“…In addition, it has also been shown that E2A and Ids proteins participate to the transcriptional regulation of the cyclin-dependent kinase inhibitors (CKIs) p21 ink4a (Id1) (Zheng et al, 2004) in different biological models including senescence. Recent studies have shown that besides p21 and p16, Id1 and Id3 are also involved in the regulation of p27 protein, notably in Xenopus neural crest progenitors (Kee and Bronner-Fraser, 2005) and in Epstein-Barr virus infected cells (Everly et al, 2004); however, the molecular basis of this inhibition has never been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Id-2 in chick which is merely involved in NC cell specification, Id-3 plays an essential role in their proliferation and survival as well as in the maintenance of a precursor pool of NC cells. 200,201 Coordination of transcriptional regulator activity during NC cell delamination. The above descriptive and functional studies indicate that NC cell delamination is achieved through cooperation of multiple transcriptional regulators in addition to members of the Snail, Zeb and bHLH families.…”
mentioning
confidence: 99%